Pengaruh Terapi Musik Keroncong Terhadap Insomnia pada Menopause di Wilayah Kerja Puskesmas Kota Tengah Kota Gorontalo - Nurnaningsih Ali Abdul; Nancy Olii (Jurnal Sehat Mandiri, 2021)
Insomnia is more common in menopausal women. In menopausal women, 50 % of the most common is hard to be in a state of sleep and wake up too early. Non-pharmacological therapy can be done using keroncong music. In essence, keroncong music can break through a person's state of consciousness and can cause psycho-physiological responses. As this process continues, it will follow the remaining state of consciousness, increasing the sensory phase, so that it can dream and sleep normally. This study aimed to analyze the effect of keroncong music on the level of insomnia in menopause in the working area of Kota Tengah public health center, Gorontalo city. This research used a pre-experimentaal design with pretest posttest group to analyze the effeect of keroncong music therapy on insomnia. The sample in this study were 60 menopausal women. The results of statistical tests using the Nonparametric Wilcoxon sample, obtained α = 0.05 with a value of ρ = 0.002 (ρ <α). It means that there was an effect of keroncong music therapy on insomnia in menopausal women. The conclusion is was an effect of keroncong music therapy on insomnia in menopausal women. it is hoped that with this research, keroncong music can be used as an alternative method that is easy, safe, and without risk to treat insomnia in menopausal women so that it can be applied in everyday life.